Visitors perception on eco-guides performance in Bako national park - Nurul Atiyah Binti, Rosdi (Universiti Malaysia Sarawak, UNIMAS, 2013)
Ecotourism is defined as a form of tourism with its primary goal is to foster sustainability through resource conservation, cultural revival and economic development. The purpose of this research project was to assess visitors perception on the important quality attribute of eco-guides and the performance of eco-guides based on the quality attributes in Bako National Park. The data were analysed by using Microsoft Excel and Statistical Package for Social Science (SPSS) software.The most important quality attribute was good communication skill while the most least important quality attribute is use of stories. The highest performance quality of eco-guide was on respect visitors from other culture. The relationship between importance of quality attributes and performance of eco-guides was studied by using Importance-Performance Analysis (IPA).